Conhecimento e formas de utilização de plantas medicinais em duas comunidades rurais: agricultores familiares de Santa Albertina (SP) e assentados de Ilha Solteira (SP) - Bueno, Aline Raia [UNESP] (2015)
The knowledge and use of medicinal plants by human beings is ancient and follows them since the beginning of civilization, and the study of this field is named ethnobotany. This work analyzed two rural populations about cultivation, use and indication of medicinal plants for symptoms and/or diseases which affect families. 35 family farmers from Santa Albertina (SP) and other 35 from Estrela da Ilha Settlement in Ilha Solteira (SP) were studied through a survey directly applied in the rural settlements. As a result, among the farmers from Santa Albertina, on which 85,72% of people who answered the questions were women and the predominant education was (74,28%) incomplete elementary school. 153 medicinal plant uses were mentioned, referring to 49 different species; while about cultivation 58 different medicinal plant species were found in the studied areas. Among the farmers from Estrela da Ilha Settlement, 48,57% of people who answered were women, 31,43% were men and 20% the couple (both answered together); most of them (60%) didn't complete elementary school (11,42%) had never gone to school. With this group, 170 uses referring to 46 different medicinal plant species; about cultivation, the diversity was bigger in Ilha Solteira (SP), with 75 different species in the studied areas. Among them, the most cultivated plants (Chenopodium ambrosioides L., Cymbopogon citratus (Dc.) Stapf., Mentha sp., Plectranthus barbatus Andr.) were also the ones with the highest use percentage in both towns. In both places, leaves were the most used medicinal plant type and tea was the most used way. About 60% of the studied farmers use the medicinal plants for treating problems and diseases in pets or cattle. About the use of plants named as medicinal for other purposes, the use of plants as spice was observed in Santa Albertina (SP), while at the Settlement, feeding was the most reported purpose. The knowledge sharing about using and cultivating medicinal ...